2020
DOI: 10.1186/s40164-019-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene mutational analysis by NGS and its clinical significance in patients with myelodysplastic syndrome and acute myeloid leukemia

Abstract: Background: In this study, we retrospectively summarized the differences of molecular gene mutations between MDS and AML patients, as well as the young and older age groups of MDS and AML patients. We also analyzed the response of newly diagnosed AML patients to standard DA or IA induction chemotherapy and the relationship between the chemotherapy outcome and the frequency of different gene mutation abnormalities. Methods: NGS assay covering 43 genes was studied in 93 de novo MDS and 325 non-M3 AML patients. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 48 publications
3
51
0
1
Order By: Relevance
“…Study results have demonstrated that the DNMT3A R882 mutation disrupts the normal ligation of methyltransferase protein subunits, causing a dominant negative impact on DNMT3A protein function [91,92]. Multiple researchers have confirmed that DNMT3A is frequently mutated in AML patients (13.5-23%) [3,93,94]. DNMT3A plays a unique role in hematopoiesis and AML pathogenesis as the inferior prognostic markers for AML patients [6,95].…”
Section: Dnmt3amentioning
confidence: 99%
See 3 more Smart Citations
“…Study results have demonstrated that the DNMT3A R882 mutation disrupts the normal ligation of methyltransferase protein subunits, causing a dominant negative impact on DNMT3A protein function [91,92]. Multiple researchers have confirmed that DNMT3A is frequently mutated in AML patients (13.5-23%) [3,93,94]. DNMT3A plays a unique role in hematopoiesis and AML pathogenesis as the inferior prognostic markers for AML patients [6,95].…”
Section: Dnmt3amentioning
confidence: 99%
“…NPM1 is frequently mutated and the incidence occur in up to 30% of AML patients overall and 40-60% of patients with normal karyotypes [3,4,60,69]. Mutated NPM1 (mNPM1) is associated with a higher complete remission, improved OS, and a lower cumulative incidence of relapse [60].…”
Section: Npm1mentioning
confidence: 99%
See 2 more Smart Citations
“…It is a heterogeneous disease accompanied by a warning mortality, where the prognosis status is dependent on cytogenetic and molecular changes as well as patient-related situations, such as age, and complications [2,3]. Furthermore, AML is a genetically heterogeneous malignant disorder of the hematopoietic system, which has been reportedly indicated to accompany with the increase of immature myeloid precursors with injured DNA [4,5]. This aggressive hematologic neoplasm often develops to relapse resulting from drug resistance despite intensive chemotherapy [6].…”
Section: Introductionmentioning
confidence: 99%